Analysis of Three Penicillin Antibiotics (Ampicillin, Amoxicillin and Cloxacillin) of Several Iranian Pharmaceutical Companies by HPLC - A. Ashnagar; N. Gharib Naseri (E-Journal of Chemistry)
Penicillin has been the most widely used antibiotic for many gram-positive bacterial infections. In this research the purity of the standard active ingredients of the various dosage forms of three penicillins (Amoxicillin, Cloxacillin and Ampicillin) imported and the purity percentage of the active ingredients in each of the various dosage forms of these drugs manufactured by several pharmaceutical companies of Iran (Kosar, Farabi and Jaber Ibn Hayan) were investigated and determined by HPLC technique. The analyses were made by using a Knauer (Germany) Spherimage-80, ODS, 2-5 μm C18 column with 30 cm length, and i.d. 4.5 mm. A 20 μL solution from each individual sample and the standard solution were injected separately onto the column of an HPLC instrument which was equipped with ECW 2000 software of Knauer, Germany. The results obtained in this research have shown that the purity percentage of the active ingredients of the standard powder and the various dosage forms of all the drugs used, were 100%.